2019
DOI: 10.1007/s00429-019-01870-4
|View full text |Cite
|
Sign up to set email alerts
|

Common and distinct neural correlates of dual-tasking and task-switching: a meta-analytic review and a neuro-cognitive processing model of human multitasking

Abstract: Although there are well-known limitations of the human cognitive system in performing two tasks simultaneously (dual-tasking) or alternatingly (task-switching), the question for a common vs. distinct neural basis of these multitasking limitations is still open. We performed two Activation Likelihood Estimation meta-analyses of neuroimaging studies on dual-tasking or task-switching and tested for commonalities and differences in the brain regions associated with either domain. We found a common core network rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(82 citation statements)
references
References 214 publications
1
75
0
Order By: Relevance
“…The findings that prefrontal stimulation improved the task switching ability and that this improvement equally affected the performance when switching to a non-inhibited task as well as when re-engaging an inhibited task (without affecting no-switch trials) support the idea that the prefrontal cortex has a role in cognitive control processes involved in task set switching, and they are consistent with previous imaging and ERPs studies. The role of prefrontal cortex in task switching has been largely documented (see [33] for a review), and neuroimaging studies have shown prefrontal activations across a variety of stimuli and paradigms (see [34] for a meta-analysis). The lateral PFC activity has been frequently interpreted as reflecting transient cognitive control operations associated with task switching, such as the endogenous task-set reconfiguration [21].…”
Section: Discussionmentioning
confidence: 99%
“…The findings that prefrontal stimulation improved the task switching ability and that this improvement equally affected the performance when switching to a non-inhibited task as well as when re-engaging an inhibited task (without affecting no-switch trials) support the idea that the prefrontal cortex has a role in cognitive control processes involved in task set switching, and they are consistent with previous imaging and ERPs studies. The role of prefrontal cortex in task switching has been largely documented (see [33] for a review), and neuroimaging studies have shown prefrontal activations across a variety of stimuli and paradigms (see [34] for a meta-analysis). The lateral PFC activity has been frequently interpreted as reflecting transient cognitive control operations associated with task switching, such as the endogenous task-set reconfiguration [21].…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there also is a well-established link between left IFJ and task switching, set shifting, or updating task representations Derrfuss et al, 2005;Worringer et al, 2019), that is, processes that allow adjusting behavior to new external demands in a top-down fashion (i.e., cognitive flexibility). This notion is also supported by repetitive transcranial magnetic stimulation studies (Higo et al, 2011;Zanto et al, 2011), pointing to IFJ's causal participation in updating task representations and regulating neural excitability in visual areas according to the task goal.…”
Section: Left Ifjmentioning
confidence: 99%
“…Therefore, currently, a particular interest was to investigate the AVI effect when the attentional recourse was competed by additional distractors during simple audio-visual processing. Because the single-task and dual-task were supported by distinct neural mechanisms (Worringer et al, 2019), we hypothesized that the attentional load affected AVI regardless of attentionalload conditions, but modulation of attentional load on AVI effect was different when the attentional load was from single-and dual-task. In order to test this hypothesis, an AV discrimination task, for evaluating the AVI effect, was applied individually or accompanied by a simultaneous rapid serial visual presentation task (RSVP), for manipulating attentional load by competing attentional recourse with AV discrimination task (Ho et al, 2009).…”
Section: Introductionmentioning
confidence: 99%